The colonial legacy: Income inequality in former British African colonies - A. B. Atkinson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper examines the distribution of top incomes in 15 former British colonies in Africa, drawing on evidence available from income tax records. It seeks to throw light on the position of colonial elites during the period of British rule. Just how unequal were incomes? How did the position of the rich in the colonies compare with that of the rich in the United Kingdom? It investigates how income concentration evolved in the last years of colonial rule, as the British government became more concerned with development, and establishes the degree of inequality at the time of independence in the late 1950s and early 1960s. What was the colonial legacy? How far did colonial inequality persist post-independence?
Keywords: I31; N37; O15; 330; inequality; income distribution; colonial Africa